Uso de los Brasinoesteroides y su beneficio en el cultivo de Cacao (Theobroma cacao L.) - Díaz Sánchez, Cinthia Joselyn (2022)
This document details the use of Brassinosteroids and their benefit in the cultivation of Cocoa (Theobroma cacao L.). Brassinosteroids are plant compounds that have the ability to stimulate plant growth. They have been shown to influence germination, rhizogenesis, flowering, senescence, abscission, and maturation processes. The conclusions show that brassinosteroids are natural compounds that are found in small amounts in plant organs, mainly found in pollen, leaves, buds, flowers and seeds, characterized as polyhydroxyphenolic compounds; At present, more than 45 members of the brassinosteroid family are known, which is why they constitute a wide family of compounds with powerful biological activity, showing that they influence germination, rhizogenesis, flowering, senescence, abscission and in the maturation processes, and that is why they are considered as the sixth group of phytohormones and despite the absence of research on cocoa with applications of brassinosteroids, it can be attributed that these would improve the floral development of cocoa, inhibit the proliferation of diseases and in turn would increase the production of ears of the plantation.